Impact of Human Resource Management Practices on Corporate Entrepreneurship - WAQAR KHAN; M. ATIQ RAFIQUE KHATTAK; SHAHBAZ AHMED; SHAHZAD KHAN (Journal of Business & Tourism, 2021)
This study aims at learning about the Human Resource Management Practices and their effects on Corporate Entrepreneurship (CE). HRM is one of the most crucial departments of all firms as it brings creativity and novelty, in products and services in order to have a competitive edge over rest concerned firms in the market. By properly managing HR an organization can bring this uniqueness. When resources are invested to bring improvement in organizational performance in terms of development in existing products and processes or expansion in product-lines or introducing new idea into practice for economic gain, the process is called corporate entrepreneurship. HRM practices play a vital role in fostering CE. Here, in this study three HRM practices; Training and development (T&D), Reward and Compensation (R&C) and Recruitment and Selection (R&S) are discussed and their impact on corporate entrepreneurship is checked out. This study is based on data that was gathered through questionnaire survey around Industrial estate Hattar (Haipur), PAKISTAN. Results show that there is significant positive relationship between the prescribed human resource management practices and corporate entrepreneurship.